Complementary health approach to quality of life in menopausal women: a community-based interventional study - Jayabharathi B (Dove Medical Press, 2014)
Baskaran Jayabharathi, Arulappan Judie SRM College of Nursing, SRM University, Kattankulathur, Kancheepuram District, Tamil Nadu, India Background: Menopause is the stage when the menstrual period permanently stops, and is a part of every woman’s life. It usually occurs between the ages of 40 and 60 years, and is associated with hormonal, physical, and psychological changes. Estrogen and progesterone levels play the biggest part in menopause. In this stage, the ovaries make less estrogen and progesterone. When the body produces less of these hormones, the parts of the body that depend on estrogen to keep them healthy will react and this often causes discomfort for women. This study tested the impact of a complementary health approach to quality of life in menopausal women. Methods: A community-based interventional study was conducted in selected areas in Kattankulathur Block, Kanchipuram District, Tamil Nadu, India. A simple random sampling technique was used to select menopausal women for the study. Of 260 menopausal women identified, 130 were allocated to a study group and 130 to a control group. The study group underwent yoga training for 1.5 hours per day on 5 consecutive days. After the 5-day intensive yoga training program, the menopausal women practiced yoga daily at home for 35–40 minutes a day. Along with daily yoga practice, they underwent group yoga practice for 2 days a week under the supervision of one of the investigators until 18 weeks. The yoga training program consisted of Yogasanas, Pranayama (breathing exercises), and meditation. The standardized World Health Organization QoL BREF scale was used to assess the women’s quality of life. We distributed an instruction manual on steps of selected yoga practice for the women’s self-reference at home after the 5 days of continuous yoga practice. A yoga practice diary was used to confirm regular performance of yoga. The women in the control group did not participate in the yoga program; however, on completion of the study, these women received intensive yoga training for 5 days.Results: There was an extremely high statistically significant difference (P=0.001) between the study group and the control group with regard to the physical, psychological, social, and environmental domains of quality of life after 6, 12, and 18 weeks of yoga therapy. The mean gain score was high in all the domains of quality of life in the study group at weeks 6, 12, and 18. The overall mean gain score in the study group was 31.58 versus 1.61 in the control group. The overall mean gain score difference was 29.97 in all domains of quality of life between the study group and the control group. In the study group, the physical, psychological, social, and environmental domains of quality of life were greatly improved by practicing yoga for 18 weeks. No adverse events were reported by the women after yoga practice.Conclusion: Quality of life in menopausal women was greatly improved after 18 weeks of yoga practice. Women who regularly practice yoga find that they are able to enjoy menopause and experience the freedom, liberation, and energy that it brings. We conclude that yoga is an effective complementary health approach for improving quality of life in menopausal women. Keywords: complementary health approach, yoga, quality of life, menopause